Development of the MARIBANG Pop-Up Book as a Learning Medium for Seventh-Grade Students at State Junior High School - Bulkani, Bulkani; Rahmaniati, Rita Rahma; Safiyah, Nur (JTAM (Jurnal Teori dan Aplikasi Matematika), 2026)
This study aimed to develop and evaluate the feasibility of the MARIBANG Pop-Up Book as an innovative learning medium for seventh-grade students at SMPN 2 Sampit. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were 36 seventh-grade students, while the object of the research was the MARIBANG Pop-Up Book learning media. Data were collected through expert validation questionnaires, student and teacher response questionnaires, and learning outcome tests. The data were analyzed using descriptive statistics and N-gain analysis to measure improvements in students’ learning outcomes. The results indicated that the MARIBANG Pop-Up Book demonstrated a very high level of validity based on evaluations from material, media, and language experts. In terms of practicality, both students and teachers gave very positive responses, indicating that the media was easy to use and engaging in classroom learning. Furthermore, the effectiveness of the media was confirmed by a significant increase in students’ learning outcomes, as reflected in the N-gain scores and classical learning completeness. These findings suggest that the MARIBANG Pop-Up Book is a valid, practical, and effective learning medium. This study highlights the potential of pop-up book–based media to enhance student engagement and learning achievement, and provides practical implications for the development of interactive instructional media in junior high school education.